Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Di Instalasi Gawat Darurat (IGD) Pada RSUD Kayuagung - Tutik Pebrianti; Mustikawati; Muhammad Iqbal (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
This study entitled The Effect of Service Quality on Patient Satisfaction in the Emergency Room (IGD) at Kayuagung Hospital. The purpose of this study was to determine the effect of the relationship quality of service on patients in the Emergency Room (IGD) at Kayuagung Hospital. The object of this research was carried out in the Emergency installation (IGD) RSUD Kayuagung. The sample in this study was 97 respondents who came from patients who had been treated in the Emergency Room (IGD) RSUD Kayuagung. The research method in this study used data collection techniques through questionnaires, using the simple random sampling technique. And the data collection techniques used validity test, reliability test, t-test statistic (t-test), coefficient of determination, and simple linear regression analysis. The results showed that there was a positive and significant effect of service quality on customer satisfaction. This result was obtained from the calculation of the t-test value > t-table (5.484 > 1.661) and was significantin thein umber (0.000 < 0.05). And from the result of the coefficient of determination obtained was 23.2%.